Family business in emerging markets: The case of Malaysia - Ibrahim, H.; Samad, F.A. (Academic Journals, 2010)
This paper explores the insight and perspective of family ownership in the context of emerging market. By highlighting the various definitions of family ownership, this conceptual approach thoroughly scrutinize the pro and cons of family ownership. Indeed, the vast literatures of family ownership has been compiled which revealed the significance of family firms throughout the world and in Malaysia. Thus, the development of family business in Malaysia has contributed in producing numbers of tycoons with their respective business field. In this paper, 40 richest families have been highlighted in Malaysia who has been instrumental in shaping the corporate scene. These millionaires have joined the list which in return undeniably contributed towards Malaysian economic growth. The contribution of family firms is indispensable and their roles are getting significant from time to time.